Sepsis-associated encephalopathy is septic - Mazeraud, A. (2018)
Institut Pasteur. Department of Infection and Epidemiology. Paris, France / Centre Hospitalier Sainte Anne. Medical and Surgical Neurointensive Care. Paris, France / Université Paris Descartes. Paris, France.